Metode Problem Solving sebagai Upaya Meningkatkan Hasil Belajar Fikih Siswa - Ani Yulianita; Imam Mardhotillah (Ta'lim: The Islamic Religious Educational Journal, 2026)
The Fiqh subject, particularly the chapter on Taharah (Purification), is often considered unimportant, which is usually caused by the teacher’s less engaging delivery of the material, resulting in suboptimal student learning outcomes. To address this issue, many suitable and interesting teaching methods can be used, one of which is the Problem-Solving Method. This study discusses the use of the Problem-Solving Method to improve students’ learning outcomes in the Fiqh subject, chapter on Taharah, for Class VIIB at MTs Sabilul Chalim Leuwimunding. The research method used was Classroom Action Research (CAR), conducted in two cycles. Data collection utilized observation techniques, tests, research instruments, and documentation conducted directly during the research. Based on the research results, 28 students, or ? 80%, achieved mastery, indicating that the success target was met. In the pre-cycle stage, the mastery percentage was only 64.29%, reflecting low student understanding. This increased to 75% in cycle I, though it had not yet met the success indicator. In cycle II, mastery rose significantly to 92.86%, categorized as very good. Thus, based on these findings, it can be concluded that the Problem-Solving Method is effective in improving students’ learning outcomes in the Fiqh subject, chapter on Taharah, for Class VIIB at MTs Sabilul Chalim Leuwimunding in the 2024/2025 academic year.At the end of the thesis, the author offers suggestions to both teachers and students, focusing on improving future educational situations.